3D geospatial visualizations: Animation and motion effects on spatial objects. (February 2018) - Evangelidis, Konstantinos; Papadopoulos, Theofilos; Papatheodorou, Konstantinos; Mastorokostas, Paris; Hilas, Constantinos
Abstract: Digital Elevation Models (DEMs), in combination with high quality raster graphics provide realistic three-dimensional (3D) representations of the globe (virtual globe) and amazing navigation experience over the terrain through earth browsers. In addition, the adoption of interoperable geospatial mark-up languages (e.g. KML) and open programming libraries (Javascript) makes it also possible to create 3D spatial objects and convey on them the sensation of any type of texture by utilizing open 3D representation models (e.g. Collada). One step beyond, by employing WebGL frameworks (e.g. Cesium.js, three.js) animation and motion effects are attributed on 3D models. However, major GIS-based functionalities in combination with all the above mentioned visualization capabilities such as for example animation effects on selected areas of the terrain texture (e.g. sea waves) as well as motion effects on 3D objects moving in dynamically defined georeferenced terrain paths (e.g. the motion of an animal over a hill, or of a big fish in an ocean etc.) are not widely supported at least by open geospatial applications or development frameworks. Towards this we developed and made available to the research community, an open geospatial software application prototype that provides high level capabilities for dynamically creating user defined virtual geospatial worlds populated by selected animated and moving 3D models on user specified locations, paths and areas. At the same time, the generated code may enhance existing open visualization frameworks and programming libraries dealing with 3D simulations, with the geospatial aspect of a virtual world. Highlights: Prototype implementation of an open 3D geovisualization software application. GIS handled interactivity between 3D models, feature layers and 3D terrains. Dynamic virtual living geospatial worlds with animated and moving spatial objects. Enhancing existing open visualization frameworks with geospatial functionalities. Challenges for creating geovisualized event and phenomena simulations.